PENYULUHAN BANTUAN HUKUM DAN PEMBERDAYAAN MASYARAKAT DI DESA PERMATA KECAMATAN BONE KABUPATEN BONE BOLANGO - Podungge, Abdul Wahab; Nuna, Muten; Tabo, Sarfan; Junus, Dikson; Napir, Suaib; Hunawa, Robby; Sahi, Nirmala A.; Arsjad, Muh. Fachri; Walahe, Dewi; Harun, Nur Istiyan; Polinggapo, Jefri; Paweni, Lisnawati; Hasan, Silvana; Bilondatu, Nikma; Biongan, Ahiar; Bantali, Endang; Ahmad, Febriyanto (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STISIPOL Candradimuka, 2025)
One way to improve community well-being is by fostering understanding and awareness so that citizens comply with applicable norms and regulations. In this community service program (PKM), participants receive knowledge in three main areas: legal aspects, community empowerment, and welfare. This approach uses a systematic delivery method and interactive question-and-answer sessions so that residents can directly participate. This approach is designed to ensure effective and equitable dissemination of knowledge. After the presentation session is complete, the activity moves to a more in-depth and collaborative stage, namely an interactive question-and-answer session. This session is deliberately designed to encourage active participation from the community as participants, creating a lively discussion atmosphere and allowing for the direct exchange of ideas and clarification of questions. The impact of the activity is evident in the increased understanding, both at the individual and group levels, of the Indonesian legal system and the mechanisms for accessing free legal aid. Furthermore, there is a growing awareness of optimizing village potential, both human and natural resources, with better quality, as well as enthusiasm for starting new businesses that are expected to stimulate local economic growth and improve the welfare of the village community as a whole. With a better understanding of the law and economic potential, it is hoped that the Permata Village community will be more proactive in utilizing local resources and building self-reliance. The success of the interaction and active participation indicates that this type of outreach has a positive long-term impact in encouraging improvements in their quality of life and future well-being.